2022
DOI: 10.1177/10748407221090274
|View full text |Cite
|
Sign up to set email alerts
|

“Failed” Matches, Child Removals, and Disrupted Placements: Devastating and Invisible Losses During the Family-Building Journey for LGBTQ Adoptive Parents

Abstract: Reproductive loss, which includes miscarriage and nongestational loss, such as adoption loss, is rarely recognized as part of the family-building journey. Such loss tends to be even more invisible among LGBTQ individuals. The current study examines the experiences of 80 LGBTQ individuals who experienced adoption-related losses (i.e., failed adoption matches, child removals, disrupted child placements), with attention to how these losses impacted them and what enabled them to move forward. Participants who purs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…Many people argue about the trauma that persists long after the disruption occurs, even though the children have spent relatively short periods with the family. These findings are consistent with those of Goldberg and Allen (2022), who studied 80…”
Section: Lack Of Supportsupporting
confidence: 92%
See 1 more Smart Citation
“…Many people argue about the trauma that persists long after the disruption occurs, even though the children have spent relatively short periods with the family. These findings are consistent with those of Goldberg and Allen (2022), who studied 80…”
Section: Lack Of Supportsupporting
confidence: 92%
“…According to Schmidt et al (1988) , the adopters experienced the loss of the child following disruption, like the loss of a person through death. These results are supported by a recent study conducted by Goldberg and Allen (2022) on LGBTQ adopters. In the study led by O’Neill (1993) , some parents reported anger and regret, while others felt shame or guilt.…”
Section: Introductionsupporting
confidence: 87%
“…One of the reasons that I have become more bold in exploring difficult topics within families and members of the LGBTQ+ community is that I have more professional power and social capital than I did in the past. As my scholarship and professional identity have become more established, I have continued to delve into research on a number of challenging topics, including same‐sex divorce (Goldberg & Romero, 2019), trans college students' help‐seeking (Goldberg, Kuvalanka, Budge, et al, 2019), postpartum depression in bisexual women (Goldberg, Smith, & Ross, 2020), and reproductive and adoption loss within LGBTQ+ parent families (Goldberg & Allen, 2022). I have also sought to act as a mentor to students and junior colleagues who wish to explore messy topics and/or marginalized communities, cognizant that it is the institutional structures of heterosexism, racism, classism, and cissexism that often result in the silencing of ideas.…”
Section: Politicalmentioning
confidence: 99%
“…Ferraro and Lucier-Greer (2022) demonstrate the benefits of decreasing overt conflict and promoting self-efficacy in reducing the adverse mental health symptomology of divorced coparents. A pair of articles by Goldberg and Allen (2022a, 2022b) speak to the experiences of LGBTQ families in health care contexts. Specifically, Goldberg and Allen (2022a) demonstrate how reproductive losses can also occur outside of the context of miscarriages or pregnancy losses and highlight the consequences and sources of resilience relied upon by LGBTQ parents experiencing nongestational losses when attempting to transition to parenthood via assistive reproductive technology, adoption, or fostering.…”
Section: The Special Issue On Supporting Structurally Diverse Familiesmentioning
confidence: 99%
“…A pair of articles by Goldberg and Allen (2022a, 2022b) speak to the experiences of LGBTQ families in health care contexts. Specifically, Goldberg and Allen (2022a) demonstrate how reproductive losses can also occur outside of the context of miscarriages or pregnancy losses and highlight the consequences and sources of resilience relied upon by LGBTQ parents experiencing nongestational losses when attempting to transition to parenthood via assistive reproductive technology, adoption, or fostering. In a second article, Goldberg and Allen (2022b) provide a phenomenological examination of how LGBTQ parents navigate asymmetry in genetic/gestational parent status, and experiences of invalidation from outside parties (which may occur particularly frequently in health care contexts).…”
Section: The Special Issue On Supporting Structurally Diverse Familiesmentioning
confidence: 99%